Development Strategy of Waqf through The Instrument of The Testament of Sharia Insurance Policy - Dewi, Mariana Puspa; Nengsih, Ifelda (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
Previous research tends to discuss the management of waqf assets obtained from testament waqf, but this study focuses on the management of the instrument of testament waqf that is attached to life insurance by PT.AXA Financial Indonesia. This study aims to determine the waqf management strategy through the instrument of the testament of the sharia insurance policy. The type of this research is field research, the source of the data is the AXA agency, and customers by conducting in-depth interviews. The results show that: 1) Waqf management is used to build assets such as mosques, prayer rooms, Islamic boarding schools, and madrasas, 2) The opportunity is that waqf management can be integrated online, and also collaborate with various waqf distribution agencies in Indonesia. The obstacles that occur are the lack of public understanding of the testament of the sharia insurance policy, and 3) The development strategy is integrated socialization to the public through various means and media. It is concluded that the waqf instrument is an alternative to carrying out worship after death, even though the public is not too familiar with the use of this instrument, it is an obligation for all insurance agents at PT. AXA to socialize this Instrument so that it can be an attraction for insurance.